2010
DOI: 10.1016/j.forpol.2009.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Development of timber framed firms in the construction sector — Is EU policy one source of their innovation?

Abstract: To enhance competition in the construction industry, EU policies have created and harmonised functional building codes. Moreover, many actors advocate the construction industry moves towards a lean production, process-based way of working for quality and cost reasons. Here, TimberFramed Engineering approaches are considered to have a competitive and environmental advantage. There is however underlying concerns that conservatism in the construction industry, and lack of timber engineering skills, may be obstacl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 22 publications
2
44
0
Order By: Relevance
“…To achieve seven floors, some measures had to be taken, the most spectacular of which is probably the concrete cage staircase open to the outside (ReThinkWood 2014). Roos et al 2008;Tykkä et al 2010;Nolan 2011;Manninen 2014;Robichaud 2014;Hurmekoski et al 2015;Roth 2015). Indeed, O'Connor et al (2004) indicated that technology transfer was an obvious obstacle to the adoption of wood, referring directly to the ability of architects and engineers to handle the concepts of timber construction.…”
Section: Motivations and Barriers Linked To Using Wood In Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve seven floors, some measures had to be taken, the most spectacular of which is probably the concrete cage staircase open to the outside (ReThinkWood 2014). Roos et al 2008;Tykkä et al 2010;Nolan 2011;Manninen 2014;Robichaud 2014;Hurmekoski et al 2015;Roth 2015). Indeed, O'Connor et al (2004) indicated that technology transfer was an obvious obstacle to the adoption of wood, referring directly to the ability of architects and engineers to handle the concepts of timber construction.…”
Section: Motivations and Barriers Linked To Using Wood In Constructionmentioning
confidence: 99%
“…This category also encompassed several elements. 1) The conservative attitude of the sector, 2) the lack of openness, 3) a high preference for established practices (GeskinConseil 2008;Tykkä et al 2010;Hemström et al 2011b;Robichaud 2014;Hurmekoski et al 2015), and 4) the lack of standardization and organization of the industry have been mentioned several times Gaston et al 2001;O'Connor and Gaston 2004;Bysheim and Nyrud 2008;Roos et al 2008;Nolan 2011;Lehmann et al 2012). Comments on 5) the fragmentation of the industry and 6) the idea that stakeholders in non-residential construction did not interact enough with each others are also present in this document sample Williamson et al 2009;Roos et al 2010;Nolan 2011).…”
Section: Motivations and Barriers Linked To Using Wood In Constructionmentioning
confidence: 99%
“…Much of the extant work focuses on the manufacturing wood industry and forest sector (Bull and Ferguson 2006, Crespell et al 2006, Schaan and Anderson 2002, Stendahl 2009, Tykkä et al 2010). The literature is consistent with respect to both the forest sector and the general industry, showing that enhanced levels of innovation or innovativeness positively impact performance (Calantone et al 2002, Han et al 1998, Hult et al 2004, Wheelwright and Clark 1992, even in small firms (Nybakk 2009, Nybakk et al 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Callcutt (2007) categorized the business patterns of housebuilders into four groups based on project delivery process, namely, current trader, investor model, self-build, and registered social landlord build-for-sale model. Li et al (2008), Tykkä et al (2010) and Pan and Goodier (2012) have also underlined that the opportunities of innovation in business model exists in the construction processes, such as the use of lean construction, the integration of information and communication technology. In addition, stakeholders have been stressed in the literature.…”
Section: Business Model: Definitionsmentioning
confidence: 99%